Pengembangan Lembar Kerja Mahasiswa Berbasis Discovery Learning untuk Meningkatkan Kemampuan Pemahaman Konsep Kalkulus Integral - Oswaldus Dadi; Abdul Rachman Taufik (Pendidikan Matematika Universitas Muhammadiyah Bangka Belitung, 2026)
Students' low conceptual understanding of integral calculus highlights the need for innovative instructional materials that promote self-directed learning. This study aimed to develop discovery learning-based student worksheets (Lembar Kerja Mahasiswa - LKM) for integral calculus that are valid, practical, and effective in enhancing students' conceptual understanding. The study employed a Research and Development (R&D) approach using the Four-D model, which was modified into three stages: define, design, and develop. The participants were 16 undergraduate students enrolled in the integral calculus course in the Mathematics Education Study Program at Universitas Musamus. The research instruments included expert validation sheets, student response questionnaires, and conceptual understanding tests administered as pretests and posttests. The data were analyzed using quantitative and qualitative descriptive techniques. The results showed that the developed LKM met the highly valid criteria based on expert evaluations, with validity percentages ranging from 85,0% to 90,6%. The practicality test indicated that the LKM was highly practical, with student response percentages ranging from 85,5% to 89,5%. The effectiveness test demonstrated an increase in the mean student scores from 14,5 on the pretest to 84,8 on the posttest, with an average N-Gain score of 0,84, categorized as high. These findings indicate that the discovery learning-based LKM is valid, practical, and effective for use as an innovative instructional material to enhance students' conceptual understanding of integral calculus.